Mysterious α6-containing nAChRs: function, pharmacology, and pathophysiology - Yang Ke-chun; Jin Guo-zhang; Wu Jie (Acta Pharmacologica Sinica, 2016)
Neuronal nicotinic acetylcholine receptors (nAChRs) are the superfamily of ligand-gated ion channels and widely expressed throughout the central and peripheral nervous systems. nAChRs play crucial roles in modulating a wide range of higher cognitive functions by mediating presynaptic, postsynaptic, and extrasynaptic signaling. Thus far, nine alpha (α2-α10) and three beta (β2, β3, and β4) subunits have been identified in the CNS, and these subunits assemble to form a diversity of functional nAChRs. Although α4β2- and α7-nAChRs are the two major functional nAChR types in the CNS, α6*-nAChRs are abundantly expressed in the midbrain dopaminergic (DAergic) system, including mesocorticolimbic and nigrostriatal pathways, and particularly present in presynaptic nerve terminals. Recently, functional and pharmacological profiles of α6*-nAChRs have been assessed with the use of α6 subunit blockers such as α-conotoxin MII and PIA, and also by using α6 subunit knockout mice. By modulating DA release in the nucleus accumbens (NAc) and modulating GABA release onto DAergic neurons in the ventral tegmental area (VTA), α6*-nAChRs may play important roles in the mediation of nicotine reward and addiction. Furthermore, α6*-nAChRs in the nigrostriatal DAergic system may be promising targets for selective preventative treatment of Parkinson's disease (PD). Thus, α6*-nAChRs may hold promise for future clinical treatment of human disorders, such as nicotine addiction and PD. In this review, we mainly focus on the recent advances in the understanding of α6*-nAChR function, pharmacology and pathophysiology.